MadC street to canvas - Heese, Luisa 1984- (Heni Publishing, 2021)
This monograph traces, for the first time, the career of a prolific artist and muralist. From her beginnings in the 1990s as a graffiti artist in the local scene in Bautzen, Germany to large-scale public mural works on an international scale in more than 35 countries, MadC has become one of the most sought-after mural artists of our time.0For over 20 years, she has captivated global audiences with her own distinctive style of art. Characterised by abstract compositions of sweeping lines and transparent layers of vivid colours, her work has its roots in graffiti art but constantly blurs the lines between street art and fine art.0MadC has exhibited widely in art galleries and has created public murals in international locations from London (Shoreditch and Dulwich) and Berlin (Hellersdorf) to Jersey City (Journal Square) and Tahiti (Papeete). Her practice moves dynamically between the street, the studio and the gallery, making her mark in private and public spaces on a monumental scale.0Structured chronologically and lavishly illustrated, this vibrant publication charts the artist's early works through to the present day, with texts by writer and curator Luisa Heese
Keywords: Walde, Claudia -- 1980-; Bild